Study of gross alpha, gross beta and natural radioactivity in soil samples of district Muzaffarabad. Issue 17 (23rd December 2022) - Shahzadi, Chand; Jabbar, Abdul; Rafique, Muhammad; Khan, Mumtaz; Dilband, Muhammad; Hayat Satti, Khizar
ABSTRACT: Results for the specific activities of primordial radionuclides, gross alpha and gross beta activities in soil samples collected from 29 locations of Azad Kashmir are presented. Soil samples were analysed, for possible radionuclide contents and relevant health implications, by high-resolution γ-ray spectroscopy and α/β counter ASC-950-DP Protean instrument. The alpha activity varied from 77.31 ± 9.95 to 440.08 ± 16.48 Bq kg -1 with overall average value of 234.88 ± 1.69 Bq kg -1 . While beta activity varied from the minimum detection level, i.e., <MDL to 361.55±149.33 Bq kg -1, with average value for all samples estimated as 235.65 ± 149.98 Bq kg -1 . Specific activities of 232 Th, 226 Ra and 40 K were calculated using γ-ray spectroscopy and were subsequently utilised for the estimation of radiation doses and radiological hazards. Activity concentrations due to 40 K, 232 Th and 226 Ra were found in the ranges 213.54 ± 17.22 to 1205.83 ± 12.82, 26.11 ± 3.72 to 84.70 ± 4.63 and 13.74 ± 1.46 to 62.23 ± 4.29 Bq m -3, with average values 616.22 ± 29.20, 55.83 ± 5.74 and 37.91 ± 2.35 Bq m -3 respectively, whilst, activity concentration due to anthropogenic radionuclide 137 Cs was found in the range from minimum detection limit, i.e., ≤0.50 to 8.82 ± 0.83 Bq m -3 . Average value for 137 Cs sample was found as 3.43 ± 0.28 Bq m -3 . Excess lifetime cancer risk (ELCR) for indoor occupation varied from 4.94 × 10 -4 to 1.82 × 10 -3 and for outdoor occupation 1.32 × 10 -4 to 4.62 × 10 -4 . Overall excess lifetime cancer risk (ELCR) for the current study was estimated as 1.55 × 10 -3 . The average values of radionuclide, in presently investigated soil samples, were within the worldwide range (50 Bq Kg -1 ) for radium radionuclide contents whilst higher for thorium and potassium radionuclides contents. Current study results can serve as baseline data for any nuclear emergency in future and may be helpful in setting radiological map of country and devising nuclear regulatory standards for background radiations in country.